Comparative transcriptome analysis reveals deep molecular landscapes in stony coral Montipora clade - Han, Tingyu; Liao, Xin; Guo, Zhuojun; Chen, J.-Y.; He, Chunpeng; Lu, Zuhong (Frontiers in Genetics, 2023)
Coral reefs, among the most invaluable ecosystems in the world, face escalating threats from climate change and anthropogenic activities. To decipher the genetic underpinnings of coral adaptation and resilience, we undertook comprehensive transcriptome profiling of two emblematic coral species, Montipora foliosa and Montipora capricornis, leveraging PacBio Iso-Seq technology. These species were strategically selected for their ecological significance and their taxonomic proximity within the Anthozoa class. Our study encompassed the generation of pristine transcriptomes, followed by thorough functional annotation via diverse databases. Subsequently, we quantified transcript abundance and scrutinized gene expression patterns, revealing notable distinctions between the two species. Intriguingly, shared orthologous genes were identified across a spectrum of coral species, highlighting a substantial genetic conservation within scleractinian corals. Importantly, a subset of genes, integral to biomineralization processes, emerged as exclusive to scleractinian corals, shedding light on their intricate evolutionary history. Furthermore, we discerned pronounced upregulation of genes linked to immunity, stress response, and oxidative-reduction processes in M. foliosa relative to M. capricornis. These findings hint at the presence of more robust mechanisms in M. foliosa for maintaining internal equilibrium and effectively navigating external challenges, underpinning its potential ecological advantage. Beyond elucidating genetic adaptation in corals, our research underscores the urgency of preserving genetic diversity within coral populations. These insights hold promise for informed conservation strategies aimed at safeguarding these imperiled ecosystems, bearing ecological and economic significance. In synthesis, our study seamlessly integrates genomic inquiry with ecological relevance, bridging the gap between molecular insights and the imperative to conserve coral reefs in the face of mounting threats.